Digital technologies in the activity of Portuguese University Tunas: a case study at RaussTuna - Tuna Mista de Bragança - Gonçalves, Bruno F. (2022)
The covid-19 pandemic triggered the widespread use of digital technologies in practically all countries not only because of the need for organizations, companies and institutions to continue to produce, but also as a way for individuals - beings of a social nature - to communicate and interact with each other during this whole troubled period. Higher education institutions were also no exception and were forced to implement online teaching across the country so that students would not be left without access to knowledge and, consequently, regress in learning. The University Tunas that constitute themselves as musical groups and are normally assigned to these institutions (of higher education) are also an example of organizations or associations that have had to adapt to new contingencies through the latest digital technologies. This study focuses precisely on this issue of the use of digital technologies by University Tunas. However, the specific case study is the “RaussTuna - Tuna Mista de Bragança (TMB)” of the Polytechnic Institute of Bragança (Portugal). In general, we intend to understand how this group of young people use digital technologies within the scope of their activity as an associative group: What are the digital technologies adopted by the University Tunas? What restrictions do members of a Tuna have in the use of digital technologies? What suggestions can be implemented to improve the digital quality of Tuna's activities? The results point to the use of a wide range of digital technologies for different purposes, especially office tools, electronic presentation software, audio, video, management of conferences or events and social networks. Members assume that they have a set of restrictions regarding the use of technologies and because of this they need training in the area to improve their skills. Finally, Tuna members present a set of improvements both at the software and at the hardware level that eventually can be implemented to increase digital quality.